Asymptotic distinguishing of autoregressive processes - Lin'kov, Yu. N. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We study the behavior of the probability of errors of the Neumann-Pearson criterion under various null and alternative hypotheses by the results of observations of autoregressive processes.